E-SERVICE QUALITY AND ITS IMPACT ON USER SATISFACTION AND LOYALTY: A SYSTEMATIC LITERATURE REVIEW - Novriansyah Novriansyah; Rhian Indradewa; Dimas Angga Negoro; Muhammad Gunawan Alif (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This research carries a Systematic Literature Review (SLR) approach to explore the concept of E-Service Quality in various digital service sectors. By following the PRISMA protocol, as many as 53 scientific articles from the Scopus database have been systematically analyzed. The results of the study show that E-Service Quality consists of six main dimensions, namely efficiency, reliability, security, responsiveness, personalization, and service fulfillment, which synergistically shape user perception of digital service quality. However, most studies still address this dimension separately, so the understanding gained tends to be partial and not yet thorough. In addition, the utilization of cutting-edge technologies such as Artificial Intelligence (AI), Internet of Things (IoT), and real-time-based systems is still not optimally integrated within the framework of service quality. This study contributes by mapping various theoretical approaches used, ranging from grand theory, middle-range theory, to applied theory, and identifying the next research direction for the development of user-oriented digital service quality models.